2013
DOI: 10.1037/a0034878
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Section III DSM-5 diagnostic system for personality disorders in an outpatient clinical sample.

Abstract: The DSM-5 includes a novel approach to the diagnosis of personality disorders (PDs) in Section III, in order to stimulate further research with the possibility that this proposal will be included more formally in future DSM iterations. The current study provides the first test of this proposal in a clinical sample by simultaneously examining its two primary components: a system for rating personality impairment and a newly developed dimensional model of pathological personality traits. Participants were commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

43
309
5
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(360 citation statements)
references
References 56 publications
43
309
5
3
Order By: Relevance
“…Thus, when the PID-5 facet scales were used to predict the IPDS total score, the PID-5 performed even better than the PDQ-4+, although the difference was marginal (i.e., the difference in the proportion of variance explained was .02); indeed, statistical significance should not be considered synonymous with clinical relevance. This finding, as well as the moderately strong associations that were observed in this study between each PDQ-4+ PD scale and the PID-5 domain and trait scales, was consistent with previous studies which suggested that DSM-IV PDs (and DSM-5 Section II PDs) could be adequately described in terms of DSM-5 Alternative PD Model maladaptive personality traits and domains (e.g., Few et al, 2013;Hopwood et al, 2012;Miller, Few, Lynam, & MacKillop, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, when the PID-5 facet scales were used to predict the IPDS total score, the PID-5 performed even better than the PDQ-4+, although the difference was marginal (i.e., the difference in the proportion of variance explained was .02); indeed, statistical significance should not be considered synonymous with clinical relevance. This finding, as well as the moderately strong associations that were observed in this study between each PDQ-4+ PD scale and the PID-5 domain and trait scales, was consistent with previous studies which suggested that DSM-IV PDs (and DSM-5 Section II PDs) could be adequately described in terms of DSM-5 Alternative PD Model maladaptive personality traits and domains (e.g., Few et al, 2013;Hopwood et al, 2012;Miller, Few, Lynam, & MacKillop, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…22 Another evaluation supported the interrater reliability of the LPFS. 23 These are promising and important features of a rating scale. Investigations have also verified the empirical structure of the PID-5, with generally good correspondence across different samples.…”
Section: Empirical Statusmentioning
confidence: 98%
“…(e.g., Chmielewski, Bagby, Markon, Ring, & Ryder, 2014;Fruyt et al, 2013;Gore & Widiger, 2013;Thomas et al, 2012), others have not found any association (Few et al, 2013;Quilty, Ayearst, Chmielewski, Pollock, & Bagby, 2013;Suzuki, Samuel, Pahlen, & Krueger, 2015;Watson et al, 2013). The debate has focused partly on how researchers define Openness to Experience/Intellect.…”
mentioning
confidence: 99%